PENGEMBANGAN PERANGKAT PENILAIAN KONSEP DASAR MATEMATIKA SD BERORIENTASI PEMBELAJARAN KOOPERATIF TIPE TAI - Sony Irianto; Ahmad Ahmad (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2009)
This instrument is aimed at improving studen’ts motivation and achievement of the students in class C of the PGSD Department of UMP. The 47 students was divided into 12 groups of 3-5 members. The development of the instrument was carried out through classroom action research consisting of 4 cycles. This research lasted for four months. Each cycles was done according to the obtained change, design and factor under investigation. To obtain data on students motivation, achievement, and response to the use of cooperative learning tipe TAI, questionaire and individual quizd as well as group assignment were used. The result showed that there was an improvement on those aspect due to the implementation of TAI using the quizes I through IV of the mid term test, individual quiz and group assignment. Key words : Type TAI of cooperative learning, motivation, learning achievement, assessment tool.